VIOLENCE IN UNIVERSITY STUDENT´S UNIVERSITY STUDENTS’ SEXUAL BEHAVIOR AND KNOWLEDGE OF THE DEFINITION OF VIOLENCE: AN EXPLORATORY ANALYSIS IN A MEXICAN PUBLIC UNIVERSITY - Addy Rodriguez Betanzos; Ismael Chuc Pina; Alejandra Crespo Aguirre (European Scientific Journal, ESJ, 2012)
This study is an exploratory approach which objectives are to know the University of Quintana Roo (UQRoo) matriculated students‘ sexual behavior and notion of the definition of violence and identify the practices and knowledge they have about their sexual health. It is relevant for this study to identify the existence of any form of violence among students in the UQRoo since aggressive behavior during youth is a predictor for violence in the adulthood. This study is a cross descriptive work containing seven constructs already validated by other studies, both national and international. It was based on a 158-item structured interviewing and self-administered questionnaire taken by 270 matriculated students in UQRoo. Related to the concept of violence, the results of the survey participants showed that they did not identify the sexual topic as an aspect in life prone to suffering from violence nor clearly identified the concept of sexual violence. Another result is that the female group of the survey participants never identified as a form of violence their intimate partner‘s avoidance of using a birth control method. In conclusion, the moral duty for the UQRoo is to continue with qualitative and mixed studies that identify the factors that influence the existence of different forms of violence in their matriculated students especially when they may be committing violent acts without being aware. These actions will be the basis for informative and prevention programmes that will have a positive influence in matriculated students‘ personal development in a professional context like the UQRoo.